Clinical approach to sexually transmitted infections and pelvic inflammatory disease in women with acute pyelonephritis - Mi-Hee Kim; Hyojin Ahn; Soyeon Kang; Ahra Lee; Seong-Heon Wie (The Korean Journal of Internal Medicine)
Background/Aims This study aimed to investigate co-occurrence and clinical characteristics of sexually transmitted infections (STIs) and pelvic inflammatory disease (PID) in women hospitalized for acute pyelonephritis (APN). Methods This single-center retrospective study reviewed medical records of inpatients with APN from January 2019 to February 2023 and identified records of 142 patients who were referred to a gynecologist to evaluate gynecological diseases including STIs. Results Of the 142 patients, 47 were tested positive for sexually transmitted pathogens in nucleic acid amplification testing, confirming the presence of STIs. In patients with APN, those with STIs were more likely to have lower abdominal pain or cervical motion tenderness (CMT) on pelvic examination and leukocytosis (> 14.5 × 109/L) than those without STIs. Of the 93 patients who underwent pelvic examination, 34 had CMT with one or more of additional criteria for the clinical diagnosis of PID, such as abnormal vaginal discharge and leukorrhea confirmed by microscopic examination, which could be clinically diagnosed as PID. Conclusions In sexually active women with APN, it is important to evaluate the possibility of STIs and PID, considering several risk factors such as lower abdominal pain, abnormal vaginal discharge, CMT, and leukocytosis.